THE PROTECTIVE ROLE OF OMEGA-3 AGAINST GENOTOXICITY AND REPRODUCTIVE TOXICITY OF COBALT OXIDE NANOPARTICLES ACUTE TREATMENT IN MALE MICE - Hussien, Nahed A; Mohamed, Hanan R. H. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Cobalt nanoparticles (NPs), especially cobalt oxide NPs (Co3O4 NPs) are attracting unique shaped NPs that are used in different biomedical applications and medicine. Different in vitro studies report their toxic and carcinogenic effect but limited in vivo studies were present on its genotoxic potential. The present study was aimed to evaluate the genotoxic potential of Co3O4 NPs on bone marrow cells and sperms and the protective role of omega-3 in male albino mice. Methods: Animals were segregated into four groups that were orally treated for 3 consecutive days, Group 1: Negative control; Group 2: Omega-3 (250 mg/kg); Group 3: Co3O4 NPs (20 mg/kg); and Group 4: Combined group (250 mg/kg Omega-3 and Co3O4 NPs 20 mg/kg). Results: The present results show that Co3O4 NPs administration significantly increased number of micronucleated polychromatic erythrocytes (PCEs)/1000 PCEs, sperm abnormalities, and DNA damage, significantly decreased sperm motility and concentration in comparison to negative control group. However, Omega-3 administration in the combined group modulates the genotoxic potential of Co3O4 NPs in comparison to Co3O4 NPs group. Conclusion: The present study reports the genotoxic potential of Co3O4 NPs in vivo and assesses the protective role of Omega-3 administration due to its antioxidant effect.